Anatomy Studio: A tool for virtual dissection through augmented 3D reconstruction. (December 2019) - Zorzal, Ezequiel R.; Sousa, Maurício; Mendes, Daniel; dos Anjos, Rafael Kuffner; Medeiros, Daniel; Paulo, Soraia Figueiredo; Rodrigues, Pedro; Mendes, José João; Delmas, Vincent; Uhl, Jean-Francois; Mogorrón, José; Jorge, Joaquim Armando; et al.
Highlights: A novel a collaborative mixed-reality approach for anatomical dissection is presented. Mid-air interaction and interactive surfaces for reconstructing and exploring a virtual cadaver. User study with professional anatomists. Anatomists could easily access any cryosections and edit contours. Our approach encourages closely-coupled collaborations and group discussion. Graphical abstract: Abstract: 3D reconstruction from anatomical slices allows anatomists to create three dimensional depictions of real structures by tracing organs from sequences of cryosections. However, conventional user interfaces rely on single-user experiences and mouse-based input to create content for education or training purposes. In this work, we present Anatomy Studio, a collaborative Mixed Reality tool for virtual dissection that combines tablets with styli and see-through head-mounted displays to assist anatomists by easing manual tracing and exploring cryosection images. We contribute novel interaction techniques intended to promote spatial understanding and expedite manual segmentation. By using mid-air interactions and interactive surfaces, anatomists can easily access any cryosection and edit contours, while following other user's contributions. A user study including experienced anatomists and medical professionals, conducted in real working sessions, demonstrates that Anatomy Studio is appropriate and useful for 3D reconstruction. Results indicate that Anatomy Studio encourages closely-coupled collaborations and group discussion, to achieve deeper insights.